Contributions to the Atlas Florae Hungariae XII. - Kevey, Balázs; Demeter, László; Lendvai, Gábor; Molnár, Attila; Papp, László; Urbán, Sándor (Kitaibelia, 2021)
In this work, we report data supplementing the Distribution atlas of vascular plants of Hungary. Altogether 1325 data of 460 vascular plant taxa are reported as contributions to 149 quadrants in the Central European Flora Mapping grid system. The new stands of Phegopteris connectilis (NW foothills of the Vértes Hills), Sternbergia colchiciflora and Corydalis solida (Danube–Tisza Interfluve), Euphorbia angulata and Potentilla alba (Nyírség) are particularly noteworthy. In addition, new stands of numerous rare or scattered species are also listed: Allium paniculatum, A. sphaerocephalon, Asplenium adiantum-nigrum, Botrychium lunaria, Bulbocodium vernum, Clematis recta, Colchicum arenarium, Cyclamen purpurascens, Dianthus barbatus, Dictamnus albus, Doronicum hungaricum, Epipactis atrorubens, E. microphylla, E. tallosii, Equisetum hyemale, Hepatica nobilis, Hesperis sylvestris, Hordelymus europaeus, Iris aphylla subsp. hungarica, I. arenaria, I. sibirica, I. spuria, I. variegata, Jurinea mollis, Lilium martagon, Linaria biebersteinii, Linum flavum, Listera ovata, Lunaria rediviva, Lychnis coronaria, Melica altissima, Menyanthes trifoliata, Monotropa hypopithis, Muscari botryoides, Ophioglossum vulgatum, Orchis militaris, O. morio, O. purpurea, Ornithogalum brevistylum, Ornithogalum sphaerocarpum, Phlomis tuberosa, Primula veris, P. vulgaris, Pseudolysimachion incanum, Pulsatilla flavescens, Pyrola rotundifolia, Scilla vindobonensis, Scrophularia vernalis, Sedum urvillei subsp. hillebrandtii, Spiranthes spiralis, Stipa borysthenica, Stratiotes aloides, Thalictrum aquilegiifolium, Trollius europaeus, Veratrum album, Vinca herbacea, Vitis sylvestris, Wolffia arrhiza etc. Jelen dolgozatunk a Magyarország edényes növényfajainak elterjedési atlasza térképeihez tartalmaz kiegészítő adatokat, elsősorban az Alföld és a Dunántúl területéről. A részletes adatokat elektronikus mellékletben közöljük. E florisztikai adatok a közép-európai flóratérképezés raszterhálózatának 149 kvadrátját érintik. 460 fajról közlünk összesen ...